The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2001
DOI: 10.1002/jcb.1261
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of melanoma growth and metastasis by combination with (−)‐epigallocatechin‐3‐gallate and dacarbazine in mice

Abstract: (-)-Epigallocatechin-3-gallate (EGCG), a major polyphenol in green tea, was shown to have cancer chemopreventive activity. In this study, we examined the antimetastatic effects of EGCG or the combination of EGCG and dacarbazine on B16-F3m melanoma cells in vitro and in vivo. First, the antimetastatic potentials of five green tea catechins were examined by soft agar colony formation assay, and the results show that EGCG was more effective than the other catechins in inhibiting soft agar colony formation. Second… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
76
0
3

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(82 citation statements)
references
References 43 publications
(53 reference statements)
1
76
0
3
Order By: Relevance
“…This implies that sulforaphane enhances the efficiency of gemcitabine against the cancer cells, especially at lower doses, thereby minimizing its cytotoxicity to normal cells resulting in better survival. Other studies have also reported a synergistic interaction between different treatment strategies (Liu et al, 2001;Kuhar et al, 2007;Kumi-Diaka et al, 2010;Wang et al, 2011). Other studies of concurrent curcumin and chemotherapeutic drugs such as cisplatin, doxorubicin, and taxol showed that curcumin enhances the antitumor activities of the latter in various cancer cells (Chan et al, 2003;Notarbartolo et al, 2005).…”
Section: Discussionmentioning
confidence: 96%
“…This implies that sulforaphane enhances the efficiency of gemcitabine against the cancer cells, especially at lower doses, thereby minimizing its cytotoxicity to normal cells resulting in better survival. Other studies have also reported a synergistic interaction between different treatment strategies (Liu et al, 2001;Kuhar et al, 2007;Kumi-Diaka et al, 2010;Wang et al, 2011). Other studies of concurrent curcumin and chemotherapeutic drugs such as cisplatin, doxorubicin, and taxol showed that curcumin enhances the antitumor activities of the latter in various cancer cells (Chan et al, 2003;Notarbartolo et al, 2005).…”
Section: Discussionmentioning
confidence: 96%
“…EGCG has also shown beneficial effects in lung cancer by decreasing the growth of the primary tumours and metastasis when mice were intraperitoneally (i.p.) injected with B16-F3m cells [37]; however, rats with breast cancer did not improve after receiving EGCG in the drinking water [26].…”
Section: Anticarcinogenic Activity Of Polyphenols In Animalsmentioning
confidence: 99%
“…VEGF-induced signaling pathway activation is required for the biological outcomes of stimulated endothelial cell proliferation and tube formation. [10][11][12] IL-8 is a cytokine produced by a variety of cells types, including transformed and endothelial cells. In addition to being a chemotactic cytokine, IL-8 is a potent angiogenic factor in vivo and in vitro.…”
mentioning
confidence: 99%